ACE2 and vasoactive peptides: novel players in cardiovascular/renal remodeling and hypertension. (August 2015) - Mendoza-Torres, Evelyn; Oyarzún, Alejandra; Mondaca-Ruff, David; Azocar, Andrés; Castro, Pablo F.; Jalil, Jorge E.; Chiong, Mario; Lavandero, Sergio; Ocaranza, María Paz
The renin–angiotensin system (RAS) is a key component of cardiovascular physiology and homeostasis due to its influence on the regulation of electrolyte balance, blood pressure, vascular tone and cardiovascular remodeling. Deregulation of this system contributes significantly to the pathophysiology of cardiovascular and renal diseases. Numerous studies have generated new perspectives about a noncanonical and protective RAS pathway that counteracts the proliferative and hypertensive effects of the classical angiotensin-converting enzyme (ACE)/angiotensin (Ang) II/angiotensin type 1 receptor (AT1R) axis. The key components of this pathway are ACE2 and its products, Ang-(1-7) and Ang-(1-9). These two vasoactive peptides act through the Mas receptor (MasR) and AT2R, respectively. The ACE2/Ang-(1-7)/MasR and ACE2/Ang-(1-9)/AT2R axes have opposite effects to those of the ACE/Ang II/AT1R axis, such as decreased proliferation and cardiovascular remodeling, increased production of nitric oxide and vasodilation. A novel peptide from the noncanonical pathway, alamandine, was recently identified in rats, mice and humans. This heptapeptide is generated by catalytic action of ACE2 on Ang A or through a decarboxylation reaction on Ang-(1-7). Alamandine produces the same effects as Ang-(1-7), such as vasodilation and prevention of fibrosis, by interacting with Mas-related GPCR, member D (MrgD). In this article, we review the key roles of ACE2 and the vasoactive peptides Ang-(1-7), Ang-(1-9) and alamandine as counter-regulators of the ACE–Ang II axis as well as the biological properties that allow them to regulate blood pressure and cardiovascular and renal remodeling.